Effect of defect Singgora roof tiles when mixed with clay for recycling - Muhammad Firdaus Rosli (2024)
Singgora roof tiles are traditional roof sheet tiles that were widely used in Kelantan and Pattani, Thailand. Singgora roofs can easily defect due to their low strength. The aim of this study was to investigate the physical and mechanical properties of Singgora title with mixed Singgora defected powder. This research examines the development and manufacturing process of the Singgora roof tiles by fabricating a bar sample. In this research, raw clay and Singgora powder were collected and crushed using a mortar, then their particle sizes were sieved to 250 μm. Both elements are mixed together at composition and labeled as 10 wt%, 20 wt%, 30 wt%, 40 wt%, and 50 wt%. The sample was fired at 900 °C for 6 hours. Sample tests were carried out by measuring the shrinkage percentage, density, porosity, and bending. The sample showed a reduction in shrinkage of 7.30% at 10 wt%, whereas the reduction was 4.80% at 50 wt%. The bending strength increased due to the defective Singgora powder acting as a binder, which prevented damage from spreading through the pores. A significant increase in bending strength of 3.8 MPa was seen at 30 wt%. However, the strength decreases between 40 wt% and 50 wt% due to the high powder ratio. The mixed elements were characterized by using XRD.